Racism, Schooling, and the Streets: A Critical Analysis of Vietnamese American Youth Gang Formation in Southern California - Kevin D. Lam (Journal of Southeast Asian American Education and Advancement, 2012)
This paper is an analysis of the relationship between educational experiences, street life, and gang formation for Vietnamese American youth gang members in Southern California. I use critical narrative methodology to center the life and experiences of a Los Angeles area gang member. His narrative substantiates how racism in schools and on the streets works together to impact and inform gang formation. Schools were sites of inter-ethnic conflict and racialized tension, and streets were spaces for contentious interactions with the police. In addition, I place the Vietnamese American youth gang phenomenon in larger historical and political contexts such as California’s anti-youth legislation, representations of Asian American youth, and U.S. geo-politics and imperialism—factors that have serious material and ideological implications and consequences.